ANTI-INFLAMMATORY ACTIVITY OF PECTIC ENZYME-TREATED PECTIN ON LIPOPOLYSACCHARIDE-INDUCED RAW 264.7 CELLS - Huang, Cian-Song; Li, Qiao-Lin; Lo, Diana; Wang, Yuh-Tai; Wu, Ming-Chang (Journal Akademik Universitas Swiss German, 2019)
The purpose of this study was to investigate the ability and pathway of the pectic enzyme-treated (PET) pectin to inhibit the inflammation of macrophage RAW 264.7 induced by lipopolysaccharide. Results showed that PET-pectin produced from 1% substrate and 48 h reaction time had the highest antioxidative activity, thus these parameters were used to produce PET-pectin used in this study. PET-pectin showed no cell cytotoxicity to normal macrophage RAW 264.7 and reduce the nitrite secretion from LPS-induced RAW 264.7 by 20%. Finally, the expression of cytokines, including NO synthase (iNOS), nitric oxide (NO), cyclooxygenase-2 (COX-2), nuclear factor kappa-light-chain-enhancer of activated B cells (NF-?B) and tumor necrosis factor (TNF-?) were analyzed by western blot. In the western blot method, it was found that iNOS, COX-2, NF-?B, TNF-? and other proteins that activated NO production had a downtrend. It was found that PET-pectin possess promising activity to mitigate the inflammatory response.